2017
DOI: 10.1155/2017/9728324
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Monocyte Apheresis in Steroid-Dependent, Azathioprine-Intolerant/Resistant Moderate Ulcerative Colitis: A Prospective Multicenter Study

Abstract: Background Granulocyte-monocyte apheresis has been proposed for the treatment of ulcerative colitis, although it is limited by costs and variability of results. Aim To assess effectiveness of granulocyte-monocyte apheresis in patients with steroid-dependent, azathioprine-intolerant/resistant moderate ulcerative colitis. Methods Consecutive patients fulfilling inclusion criteria were prospectively enrolled, treated by apheresis, and followed up for 12 months. The primary end point of the study was steroid-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
7
2
Order By: Relevance
“…These results are in line with the outcomes in a previous study had sustained clinical remission rates of 83.3%, 68.8%, and 23.1% in corticosteroid‐naïve, corticosteroid‐dependent, and corticosteroid‐refractory patients, respectively 12 . Further, as remission‐induction therapy, GMA has shown efficacy in immunomodulator‐intolerant or refractory moderate UC patients 31–39 . However, more recent studies have shown that concomitant IMM therapy may compromise a patient's response to GMA in the maintenance phase 13,40 .…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with the outcomes in a previous study had sustained clinical remission rates of 83.3%, 68.8%, and 23.1% in corticosteroid‐naïve, corticosteroid‐dependent, and corticosteroid‐refractory patients, respectively 12 . Further, as remission‐induction therapy, GMA has shown efficacy in immunomodulator‐intolerant or refractory moderate UC patients 31–39 . However, more recent studies have shown that concomitant IMM therapy may compromise a patient's response to GMA in the maintenance phase 13,40 .…”
Section: Discussionsupporting
confidence: 87%
“…The mechanism underlying GMA involves the Adacolumn, which is filled with cellulose acetate (CA) beads, interacting with fragment crystallizable‐gamma receptor (FcγR) expressed at the surface of activated leukocytes and selectively adsorbing granulocytes and monocytes from the systemic circulation 2 . Numerous reports have described the clinical efficacy and safety of GMA in patients with active UC 3‐22 . Previous reports have demonstrated that patients who were most likely to respond to GMA tended to be first attack cases and were steroid‐naïve with short disease duration and low disease activity 9‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that patients who were most likely to respond to GMA tended to be first attack cases and were steroid‐naïve with short disease duration and low disease activity 9‐14 . However, GMA has been reported to enable the evaluation of clinical efficacy for refractory UC such as steroid‐dependent UC and immunosuppressor (IM)‐resistant UC 6,15,16 . Moreover, recent studies have described the combined efficacy of GMA with biologics 17,20 and tofacitinib 21 in patients with refractory UC.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent retrospective and prospective studies have suggested certain prognostic factors in the therapeutic response. [35][36][37] It seems that younger patients respond better to GMA therapy, whereas gender and smoking status showed no difference in response to treatment. 35 Yokoyama et al found that shorter duration of UC and lower cumulative corticosteroid dose are associated with a higher efficacy rate.…”
Section: Discussionmentioning
confidence: 97%
“…[35][36][37] It seems that younger patients respond better to GMA therapy, whereas gender and smoking status showed no difference in response to treatment. 35 Yokoyama et al found that shorter duration of UC and lower cumulative corticosteroid dose are associated with a higher efficacy rate. 36 In their study, patients who received GMA treatment immediately after relapse were the best responders.…”
Section: Discussionmentioning
confidence: 97%